The effect of underwriter’s market share, spread and management earnings forecasts bias and accuracy on underpricing of Malaysian IPOs - Ammer, Mohammed Abdullah; Ahmad Zaluki, Nurwati Ashikkin (Emerald Group Publishing Limited, 2016)
Purpose– Underpricing is one of the most important anomalies associated with initial public offerings (IPOs). The purpose of this paper is twofold; first, it examines the impact of underwriter’s market share and spread on the underpricing of IPOs; and second, it investigates the effect of management earnings forecasts bias and accuracy on the underpricing of IPOs,Design/methodology/approach– A sample of 190 Malaysian IPOs listing on the main market of Bursa Malaysia from January 1, 2002 to February 29, 2012 was used and collected data were analyzed through univariate analysis and pooled ordinary least squares regression.Findings – The empirical evidence shows that IPOs underwritten by underwriters as having high market share and charging low underwriting spread experience higher level of under pricing. The paper also finds that IPOs issued more biased earnings forecasts are related with severe underpricing. Finally, this paper reveals that the more accurate the earnings forecasts are, the more minimized will be the asymmetric information and hence, the less will be IPO underpricing.Practical implications – The paper has some implications for policy makers, investors and underwriters. First, this study offers some insights for policy makers who are responsible for Malaysian financial markets current reforms. Further, knowing the importance of the economic outcomes of the earnings forecasts on underpricing for policy makers, they may adopt the findings in their discussion of costs of litigation and potential modifications in the requirements of issuing earnings forecasts. For the investors, findings may improve their understanding of equity valuation and for the underwriters, it would assist them in identifying underwriting cost.Originality/value – This paper is considered the first study to extend IPO literature by investigating the relationships between underwriter’s market share, underwriter’s spread, earnings forecasts bias, earnings forecasts accuracy and IPO underpricing in an emerging country, such as Malaysia.